A comparison of tropical temperature trends with model predictions - David H. Douglass; John R. Christy; Benjamin D. Pearson; S. Fred Singer (International Journal of Climatology, 2008)
We examine tropospheric temperature trends of 67 runs from 22 ‘Climate of the 20th Century’ model simulations and try to reconcile them with the best available updated observations (in the tropics during the satellite era). Model results and observed temperature trends are in disagreement in most of the tropical troposphere, being separated by more than twice the uncertainty of the model mean. In layers near 5 km, the modelled trend is 100 to 300% higher than observed, and, above 8 km, modelled and observed trends have opposite signs. These conclusions contrast strongly with those of recent publications based on essentially the same data. Copyright © 2007 Royal Meteorological Society